What Do College Seniors Know About Economics? - Walstad, William; Allgood, Sam (American Economic Review, 1999)
If college seniors who have taken an economics course were asked questions that test their knowledge of basic economics, what would the results show? Would seniors give correct answers to most questions, or would they show significant deficiencies? Students are exposed to many ideas during their undergraduate education, so one would not expect them to retain all of the economic content they were taught, but one would hope that they would retain at least a knowledge of basic economics. This study investigates whether that is the case. Two data sources were used for the study. The first was from a Gallup survey of a national random sample of 300 college seniors (Walstad and Max Larsen, 1992). The survey includes 15 multiple-choice questions testing economic knowledge. The responses from that survey can be separated according to whether students took economics. The second data set came from the economics scores for 12,854 students who took the Major Field Test in Business II (MFTB) sponsored by Higher Education Assessment of the Educational Testing Service (ETS, 1998). The MFTB covers content typically taught in an undergraduate program in business and contains about 20 multiple-choice questions on basic economics. Although there are differences between the two data sets, we viewed this as an advantage for our study. Our hypothesis is that most college seniors would show relatively limited knowledge of basic economics, no matter what questions were asked or how the data were collected. We expected students responding to the Gallup questions to score higher than students taking the MFTB because the Gallup questions were simpler and designed for telephone interviews. The MFTB, by contrast, is a standardized achievement test with definitions and analytical questions of the type that would be used in course exams for Principles of Economics. With both sets of test data, however, we expected to find significant gaps in the economic knowledge of college seniors.